THE EFFECT OF RME (REALISTIC MATHEMATICS EDUCATION) AND LEARNING MOTIVATION ON MATHEMATICS LEARNING OUTCOMES - Ikhwan Mustaqim; Ahmad Noor Fatirul; Djoko Adi Walujo (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the test results: (1) The Effect of RME (Realistic Mathematics Education) and the Expository Method on Students' Mathematics Learning Outcomes, (2) The Effect of High and Low Learning Motivation on Students' Mathematics Learning Outcomes, (3) The Interaction Between RME (Realistic Mathematics Education) and Learning Motivation on Students' Mathematics Learning Outcomes. This experimental research was carried out using a 2x2 factorial design. The subjects in this study were students of class XI which consisted of four classes with 120 students. The subjects that became the focus of the experiment were classically randomized, namely four ABCD classes from SMAN 1 Sangkapura. The research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The calculation results show that: (1) Mathematics Learning Outcomes of students who are taught with RME (Realistic Mathematics Education). Low learning Based on the table it turns out that 0.013 < 0.05 then it can be said to be significant, and (3) Based on the summary of the results of the learning model and students' learning motivation on students' Mathematics Learning Outcomes. RME (Realistic Mathematics Education), Expository Method, and Learning Motivation on Students' Mathematics Learning Outcomes. Based on the results of the study, it was concluded that using RME (Realistic Mathematics Education), Expository Methods, and Learning Motivation could improve students' Mathematics Learning Outcomes.